Real of Simply Assembly Line Balancing using Fact-Model - HASOLOAN, HAERY IAN PIETER; YAAKOB, MOHD YUHAZRI; PERUMAL, PUVANASVARAN; ABD RAZAK , JEEFFERIE (International Association of Computer Science and Information Technology Press （IACSIT Press）, 2012)
This study is to examine the productivity of the designated production line related to the cycle time, takt time, non-value added activities, and product quantities in which the processing time and the number of operators are having the correlation with assembly line balancing. By using a developed simulation tool, called as Fact-Model; which having facility menus such as the graph of critical path network, working time, and production table, enable users to analyze the line assembly related to idle time and bottleneck as well as to address the unbalancing causes. Fact-Model is also facilitate users to apply their owned pictures (which is taken related to process) in order to depict and map the real characteristic of production flows. Based on the simulation carried out, where the reallocation activities in Main-Board production line are undertaken through the production process and operators reassigned, it shows that productivity is optimum.